Food safety awareness and food preferences among 4th year btte students - Payot, Cyd Magica C.; Payot, Cyd Magica C.; Almacin, Blanche G. (Digos City: UMDC, 2018)
Proper hygiene practices among food vendors are crucial in ensuring food safety and preventing foodborne illnesses. Although food vendors play a critical role in the food supply chain, foodborne illnesses and food contamination can result from inadequate hygiene practices. This study aimed to assess the food safety awareness and hygiene practices of street vendors in Digos City. Eventually, data was collected from 150 randomly selected food vendors, and answered the adopted questionnaire using a 5-point Likert scale. The study used a descriptive-comparative research design to determine the awareness level of food vendors on food safety and proper hygiene. Based on the findings, the level of awareness on food safety is high. It indicates that food safety standards are consistently upheld across food vendors. While, the level of food hygiene among food vendors was described as high, thus, this indicates that the food hygiene among food vendors is well practiced and relatively evident. Findings also revealed that there was a significant difference between food safety awareness and proper hygiene practices among vendors when analyzed by profile. Hence, the study suggests that improving food safety and hygiene standards in Digos City can lead to a reduction in foodborne diseases and overall public health by implementing food safety training for vendors and must undergo regular inspections of city health office.
Keywords: Education. -- BTTE. -- Undergraduate thesis